Planck : driven by vision, broken by war - Brown, Brandon R. 1997- (Oxford Univ. Press, 2015)
"Planck's Law, an equation used by physicists to determine the radiation leaking from any object in the universe, was described by Albert Einstein as 'the basis of all twentieth-century physics.' Max Planck is credited with being the father of quantum theory, and his work laid the foundation for our modern understanding of matter and energetic processes. But Planck's story is not well known, especially in the United States. A German physicist working during the first half of the twentieth century, his library, personal journals, notebooks, and letters were all destroyed with his home in World War II. What remains, other than his contributions to science, are handwritten letters in German shorthand, and tributes from other scientists of the time, including his close friend Albert Einstein. In Planck : Driven by Vision, Broken by War, Brandon R.^